Student Misconceptions In Elementary School When Solving Problems On Mathematical-Literacy-Based Question Types - Firstlyta Bulan Aulya Ahmad; Alifatul Hidayah; Zaenal Abidin (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2025)
The purpose of this study is to characterizes the challenges that students encounter when attempting to solve mathematical literacy problems. Indonesia's disappointing performance on PISA 2022 assessment, scoring roughly 366 well below the OECD average reflects how misconceptions surrounding fundamental mathematical concepts continue to pose a significant challenge, especially among elementary school students. The study involved Grade 5, Phase C students who had already covered the relevant material and were subsequently given literacy-based mathematics problems across two testing phases: an initial phase designed to pinpoint students' core difficulties, followed by a second phase intended to confirm the researchers' preliminary analysis. Data were examined through a descriptive qualitative approach, with findings interpreted using misconception indicators drawn from established expert frameworks. To support the written assessments, the researchers conducted informal interviews while students worked through the problems, and these conversations corroborated the patterns observed in the test results. The analysis revealed that students' primary struggles stemmed from misconceptions occurring across the formulating, employing, and interpreting stages of problem-solving. Errors were most concentrated in the employing stage, 50% of all mistakes finding that led the researchers to recommend a structured, context-driven instructional approach combined with Problem-Based Learning (PBL) to strengthen students' mathematical literacy.